2016
DOI: 10.5398/medpet.2016.39.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol as an Energy Source for Ruminants: A Meta-Analysis of in Vitro Experiments

Abstract: Glycerol or glycerin is generally recognized as a safe compound to be used in animal feed, especially for ruminants. A number of in vitro studies related to glycerol supplementation in ruminant ration have been published but to date the results have not been summarized. The objective of this study was, therefore, to evaluate in vitro digestibility, ruminal fermentation characteristics, total gas and methane production through the meta-analysis approach. Meta-analysis was applied to 13 experiments and 42 treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(57 reference statements)
3
7
0
1
Order By: Relevance
“…This study revealed that the different additives had no detrimental effect on IVDMD and IVOMD of both non-ensiled and ensiled cassava leaves. These results were in agreement with both of the previous meta-analysis in vitro study in which glycerol supplementation was used as an energy source for ruminants (Syahniar et al 2016) and the addition of low level tannin showed a lower adverse effect on digestibility (Jayanegara and Palupi 2010). On the contrary, the present study indicated that ensiling significantly increases the percentage of IVDMD and IVOMD as shown by lower NDF and ADF contents of the cassava leaves after ensiling.…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that the different additives had no detrimental effect on IVDMD and IVOMD of both non-ensiled and ensiled cassava leaves. These results were in agreement with both of the previous meta-analysis in vitro study in which glycerol supplementation was used as an energy source for ruminants (Syahniar et al 2016) and the addition of low level tannin showed a lower adverse effect on digestibility (Jayanegara and Palupi 2010). On the contrary, the present study indicated that ensiling significantly increases the percentage of IVDMD and IVOMD as shown by lower NDF and ADF contents of the cassava leaves after ensiling.…”
Section: Discussionsupporting
confidence: 92%
“…Fatty acids are not degraded or fermented by rumen microbes, but unsaturated fatty acids are hydrogenated into various fatty acid isomers with higher saturation degree and carried out mainly by Butyrivibrio fibrisolvens and Clostridium proteoclasticum [ 30 , 31 ]; such hydrogenation process does not generate gas. Although fermentation of glycerol in the rumen produces gas [ 32 ], the amount is relatively small [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While, other studies reported that using glycerol with dairy cows resulted in either an increase (Kass et al, 2012) or a reduction in DM intake (Boyd et al, 2013). However, the use of glycerol, propylene glycol and calcium propionate as glucogenic mixture precursors is based on in vivo and in vitro studies reporting that the supplementation increased the ruminal propionic concentration (Chanjula et al, 2014;Sanchez et al, 2014;Mesilati-Stahy et al, 2015;Syahniar et al, 2016;Yao et al, 2017). Post-absorption, the elevated propionate increases plasma glucose concentration, which has also been shown to lead to concomitant increases in blood insulin and reduced BHBA concentrations (Mesilati-Stahy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, several studies on ruminant animals concluded that the glucogenic precursors as energy supplementations or as diets corn replacements have some positive effectiveness on feed intake, nutrients digestibility, carcass characteristics and meat quality as well as productive and reproductive performance of lactating animals (Carvalho et al, 2011;Matras et al, 2012;Omazic 2013;Kafilzadeh et al, 2015;Khattab 2015;Porcu et al, 2017). However, each of glucogenic precursors, such as glycerol (Syahniar et al, 2016;White et al, 2016), propylene glycol (Khattab 2015;Mesilati-Stahy et al, 2015), glycerin (Chanjula et al, 2014;Kafilzadeh et al, 2015) and calcium salts of propionate (Liu et al, 2010;Sanchez et al, 2014), has a different route for conversion to glucose and causing a rapid and sustained rise of blood glucose.…”
Section: Introductionmentioning
confidence: 99%